NGTS-10b: the shortest period hot Jupiter yet discovered. Issue 1 (20th February 2020) - McCormac, James; Gillen, Edward; Jackman, James A G; Brown, David J A; Bayliss, Daniel; Wheatley, Peter J; Anderson, David R; Armstrong, David J; Bouchy, François; Briegal, Joshua T; Burleigh, Matthew R; Cabrera, Juan; et al.
ABSTRACT: We report the discovery of a new ultrashort period (USP) transiting hot Jupiter from the Next Generation Transit Survey (NGTS). NGTS-10b has a mass and radius of $2.162\, ^{+0.092}_{-0.107}$ M J and $1.205\, ^{+0.117}_{-0.083}$ R J and orbits its host star with a period of 0.7668944 ± 0.0000003 d, making it the shortest period hot Jupiter yet discovered. The host is a 10.4 ± 2.5 Gyr old K5V star ( T eff = 4400 ± 100 K) of Solar metallicity ([Fe/H] = −0.02 ± 0.12 dex) showing moderate signs of stellar activity. NGTS-10b joins a short list of USP Jupiters that are prime candidates for the study of star–planet tidal interactions. NGTS-10b orbits its host at just 1.46 ± 0.18 Roche radii, and we calculate a median remaining inspiral time of 38 Myr and a potentially measurable orbital period decay of 7 s over the coming decade, assuming a stellar tidal quality factor $Q^{′ }_{\rm s}$ =2 × 10 7 .